Joint bit and power loading for adaptive MIMO OFDM VLC systems. Issue 7 (8th January 2020) - Siddiqi, Umair F.; Narmanlioglu, Omer; Uysal, Murat; Sait, Sadiq M.
Abstract: Visible light communication (VLC) is a short‐range wireless access technology based on the dual use of illumination structure. The frequency‐selective characteristics of VLC channels motivate the use of orthogonal frequency division multiplexing (OFDM). In addition, the presence of multiple light sources in most indoor spaces makes multiple‐input–multiple‐output (MIMO) communication techniques a natural solution for VLC systems. In this paper, we investigate the design of an adaptive MIMO OFDM system. Specifically, we propose adaptive bit and power loading for a direct current–biased OFDM VLC system with MIMO mode switching between repetition coding and spatial multiplexing. We formulate the adaptive algorithm design as an optimization problem where we aim to maximize spectral efficiency through the proper selection of modulation order, power level, and MIMO mode, while satisfying a targeted bit error rate. To solve the underlying NP‐hard problems, we use a simulated annealing heuristic. We present Monte Carlo simulation results for a typical indoor setting and illustrate the performance improvements through link adaptation. Abstract : We propose an adaptive DCO‐OFDM system that maximizes spectral efficiency (SE) by applying the following steps. The first is the optimization of the power of the subcarriers using the Simulated Annealing algorithm. In the second and third steps, the system selects best modulation orders for the subcarriers based on a given BER value and determine SE value for both repetitive coding (RC) and spatial multiplexing (SM) modes. The system chooses either RC or SM mode, whichever yields better SE.